The Old Testament in the Life of God's People : Essays in Honor of Elmer A. Martens - Isaak, Jon M., 1960-; Martens, E. A. (Eisenbrauns, 2009)
This book celebrates the contributions to Old Testament theology of Elmer A. Martens, President and Professor of Old Testament at Mennonite Brethren Biblical Seminary, Fresno, California (both positions now Emeritus). It includes 3 essays written by Martens himself, as well as 15 others written by his former students, colleagues, friends, and even one of his professors! The essays are clustered around three topics--Christians' use of the Old Testament, aligning God's people with God's call for justice, and addressing the issue of land in the life of God's people--each of which reflects an area of special interest to Martens. A biographical sketch, a list of the honoree's varied publications, and indexes are included.Martens has had a productive career as teacher, author, and preacher--a career spanning almost six decades and five continents. After 40 years of seminary teaching, Elmer is known to many as professor. He taught his signature class, Old Testament theology, from 1968 to 2004 at Mennonite Brethren Biblical Seminary, shaping an entire generation of preachers and Bible teachers. His Old Testament theology textbook, God's Design, now in its third edition, continues to be used at the seminary as well as in translation in numerous other schools around the world.